PENERAPAN SISTEM CASH ON DELIVERY PADA SHOPEE DI INDONESIA - Meilyana Chayadi; Putri Amelia Inggriati; Afdal Iswari; Muhammad Raihan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2021)
Since Indonesia continues to extend the period of PPKM (Pemberlakuan Pembatasan Kegiatan Masyarakat), more and more Indonesians are starting to shop from home. Starting from daily needs to tertiary needs. Various ecommerce are also one of the places where Indonesian people shop from home. One of them is Shopee. This ecommerce is well known and is the number one e-commerce in Indonesia with the most users (2021, Snapchart). With the price offered relatively cheap and easy to use, this e-commerce becomes the most popular place by people to shop from home. The transactions provided are also one of the reasons Shopee is widely used by the people of Indonesia. Especially for transactions using a cash on delivery system or on-site payments. By using this system, people do not need to transfer from banks or use credit cards but simply pay with cash only. With this system, people who are far from the reach of digital payments can still shop from home. However, it turns out that there are still many Indonesian people who do not understand the payment system in this place so as to cause a lot of losses for sellers and couriers. Information about the payment system in this place has been spread in various media such as television, social media, newspaper media, and in the Shopee application itself. Unfortunately, the literacy of Indonesian people is still lacking so that the case of this cash on delivery system continues to grow. Therefore, we conducted studies and research on the application of cash on delivery systems at Shopee in Indonesia. This type of research is research based on existing data but made to be simpler to make it easier for readers to understand.